(untitled) (CIPEEX, 2022)
THE PANORAMA OF CONGENITAL SYPHILIS IN BRAZIL IS INCREASINGLY INCIDENT IN SOCIETY WITH SPECIFIC CHARACTERISTICS, REFLECTING THE CURRENT EPIDEMIOLOGICAL PROFILE OF THIS DISEASE. THE PRESENT ANALYSIS IS A MINI INTEGRATIVE LITERATURE REVIEW THAT AIMS TO PRESENT THE EPIDEMIOLOGICAL PICTURE ABOUT SYPHILIS IN THE CONGENITAL AND GESTATIONAL FORMS IN THE BRAZILIAN GEOGRAPHICAL AREA. EIGHT ARTICLES WERE USED, OF WHICH FIVE HAD ALL THE DESCRIPTORS AND FULLY MET THE OBJECTIVE, RELATED TO THE RESEARCH THEME FROM THE DECSMESH, SCIELO AND PUBMED DATABASES. ARTICLES PUBLISHED MORE THAN 5 YEARS AGO, WHICH ALSO DID NOT ANSWER THE GUIDING QUESTION, WERE EXCLUDED. THE RESEARCH SHOWED THAT THERE IS A PREDOMINANCE OF SYPHILIS, IN ITS AFOREMENTIONED TYPES, IN YOUNG WOMEN, WITH LOW INCOME AND INCOMPLETE SCHOOLING, DIAGNOSED MAINLY IN THE PRIMARY STAGE AND WITH FAILURE IN TERMS OF EARLY TREATMENT. IN GENERAL, THE RESEARCH SHOWED THAT SYPHILIS IS MORE PREVALENT IN WOMEN BETWEEN 19 AND 29 YEARS OF AGE, OF PREDOMINANTLY BROWN AND BLACK ETHNICITY, WITH LOW INCOME AND ALSO WITH LOW EDUCATION, A CHARACTERISTIC WHICH DEMONSTRATES HOW THE LACK OF INFORMATION IMPACTS CONTAMINATION BY VENEREAL DISEASES. FURTHERMORE, THIS RESEARCH DENOTED HOW THE LACK OF ADHERENCE TO THE CORRECT TREATMENT DURING THE APPROPRIATE PERIOD, ON THE PART OF THE PREGNANT WOMAN AND HER PARTNER, AND THE NEGLECT ON THE PART OF HEALTH PROFESSIONALS IN INVESTIGATING AND MITIGATING THIS DISEASE, INFLUENCES THE SCENARIO OF SYPHILIS AND ITS RECURRENCE IN PREGNANT COMMUNITY OF BRAZILIAN MODERNITY. HOWEVER, IT IS NOTEWORTHY THAT THERE WAS AN INCREASE IN THE NUMBER OF POSITIVE TESTS OF PREGNANT WOMEN FOR THE SYPHILIS BACTERIA IN BASIC HEALTH UNITS. THE ANALYZED ARTICLES HAD IN COMMON THE PARTNER’S NON-ADHERENCE TO THE TREATMENT OR INCOMPLETE TREATMENT. THE LACK OF INFORMATION ABOUT TREATMENT AND POST-FETAL COMPLICATIONS WAS EVIDENCED AS A LIMITING FACTOR. THUS, THE NEED TO CHANGE THIS REALITY IS NOTORIOUS, WHICH COULD BE DONE THROUGH PUBLIC POLICIES AND PROFESSIONAL TRAINING.